Military Barriers Representations in Palestinian Novels after Oslo Accords: A Realistic Irony Language - Kayyal, Hadeel Mohammed; Qasim, Nader Jomaa (Journal of Arabic Language Sciences and Literature, 2024)
The article discusses the impact of the presence of military checkpoints artistically on Palestinian novels and their transformation, and the diversity of the novels that reflect reality and suffering, in addition to the role of language in expressing social conflicts and the challenges of reality, and the importance of reality as a source of characters and events in novels; military barriers are mirrors of the Palestinian reality. The article also addresses the militarization of vocabulary in the novel and its connection to the language of occupation, and touches on the use of satire and comedy in Palestinian novels and its implications, as literary satire helps liberate the human ability to sharp criticism. The article emphasizes that the new Palestinian novel is characterized by its realism and its choice of simple, precise language free of ornate embellishments and rhetorical adornments.The problem of study: The study seeks to uncover the manifestations of military checkpoints and interpret them in selected novels, by tracing their representation, manifestation, and artistic impact in the novel, and what they reflect of the reality of the siege in the Palestinian context.The study aims to investigate the presence of military checkpoints, their influences, and manifestations in Palestinian literary works, as they serve as a successful model for engaging with the Palestinian reality. The study seeks to highlight the necessity of making military checkpoints a priority added to the many priorities of Palestinian literature in order to shatter them with hope for a new reality.It is concluded that the functional role of the novel relying on a daily theme to give it justice is to produce a discourse that rejects the Palestinian reality created by the occupation with its military barriers, and to produce a consistent resistance discourse in a narrative form.
Keywords: Military Barriers; Occupation; Reality; Language; Irony